Kinetic-scale Mirror Mode Storm Embedded in a Flux Rope in the Solar Wind - L. Yu; S. Y. Huang; Z. G. Yuan; K. Jiang; H. H. Wu; Q. Y. Xiong; R. T. Lin; Z. Wang; Y. T. Tang; H. Bai (The Astrophysical Journal)
Mirror modes are ubiquitous in the space plasma environment. Mirror mode storms are successive trains of mirror modes, lasting for a long time. Previous studies generally focused on large-scale mirror mode storms. However, studies concerning kinetic-scale mirror mode storms are still lacking. In this work, we report a kinetic-scale mirror mode storm embedded in a magnetic flux rope in the near-Earth solar wind for the first time. As the mirror mode instability develops from unstable to marginally stable, the structures of the mirror mode that make up the mirror mode storm present a variation from small-amplitude dense peaks to large-amplitude sparse holes. With joint observations from the Magnetospheric Multiscale mission, ACE, and Wind, it is found that this mirror mode storm has been excited before reaching the near-Earth region. This kinetic-scale mirror mode storm might be caused by compression between slow and fast plasma flows inside the flux rope. Our observations provide a possible source and mechanism for the generation of kinetic-scale mirror mode storms.